1982
DOI: 10.1128/iai.37.1.374-377.1982
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus-specific serum immunoglobulin a: detection in patients with primary or recurrent herpes infections and in healthy adults

Abstract: A sensitive radioimmunoassay was used to determine levels of herpes simplex virus (HSV)-specific immunoglobulin A (IgA) in serial serum samples drawn from patients with primary HSV infections and from persons with recurrent HSV infections, and in single samples from 90 healthy adults. Significantly rising HSV IgA titers were detected in patients with primary infections, whereas those with recurrent infections had nonfluctuating titers. Sera of IgG-seropositive healthy adults were all positive for HSV-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…In our antibody-capture assay this type of inhibition is no longer possible since IgA and IgG are separated prior to reaction with antigen. This might also explain why Friedman and Kimmel [1982] found a significant HSV-IgA response in some of their patients with primary HSV infection. Little is known about the persistence of HSV-IgA, but preliminary results suggest that it is an acute-phase antibody which may persist for approximately the same time as HSV-IgM antibody.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our antibody-capture assay this type of inhibition is no longer possible since IgA and IgG are separated prior to reaction with antigen. This might also explain why Friedman and Kimmel [1982] found a significant HSV-IgA response in some of their patients with primary HSV infection. Little is known about the persistence of HSV-IgA, but preliminary results suggest that it is an acute-phase antibody which may persist for approximately the same time as HSV-IgM antibody.…”
Section: Discussionmentioning
confidence: 97%
“…As has been stressed, class-specificity of antisera has to be determined since we as well as others [J. Wilhelm, personal communication] found that some commerical antisera to human IgM or IgA, including the one used by Friedman and Kimmel [1982], cross-react with other classes of antibody, particularly with IgG antibody. On the other hand, the differences might also be due to competititve inhibition by specific IgG antibody.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The diagnostic value of specific total serum IgA antibodies as marker of virus infections is controversial [Halonen et al, 1979a,b;Nikoskelainen et al, 1979;Friedman and Kimmel, 1982;Sarov and Haikin, 1983;Sikuler et al, 1983;Strand and Hoddevik, 1984;Guglielmino et al, 1989;Vikerfors et al, 1989;Chau et al, 19931. In contrast, different reports have shown the usefulness of virus-specific polymeric IgA as indicator of acute or recent infection [Negro Ponzi et al, 1985;Hashido et al, 1989;Kawano and Minamishima, 19921. Against this background, the presence of heterotypic enteroviral total and polymeric IgA antibodies in serum from patients with acute enterovirus infections were examined and compared with sera from patients with other infections. The presence of heterotypic enteroviral total IgA antibodies in serum samples from blood donors that were collected in different seasons was also investigated and compared.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important aspects of genital herpes (GH) is the asymptomatic infection (13). HSV-IgA serum antibody response has been found to correlate well with asymptomatic and overt genital herpes infections (10)(11)(12). In the absence of any past history of HSV infection, a rise in titre might indicate a type-specific antibody response to some occult HSV lesion at a remote site.…”
mentioning
confidence: 99%